Unite the Tribes Ending Turf Wars for Career and Business Success - Duncan, Christopher; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
No matter what business you're in, at the end of the day, it's all about people. Workers are people, and so are managers. Every day, millions of people wake up, get dressed, and go to work. The fact that all of them do different jobs and have different levels of authority has been used for ages to divide us. The truth of the matter, however, is that we're all just trying to make a living and provide for the ones we love$1 (Band that's a powerful common bond. If you can grasp that one concept, you'll have the power to change your world for the better in ways that you never dreamed possible. When you reach people at this fundamental level$1 (Bletting them know that you care about what's important to them and showing what's in it for them personally when they join forces with you$1 (Bnothing is beyond your grasp. Unite the Tribes: Ending Turf Wars for Career and Business Success presents the "Ten Pillars of the Empire" for just this purpose. You don't have to become a great charismatic leader to make them work. Each pillar speaks to you as an individual employee and shows you how to improve both your career and the company's bottom line in a practical and organized manner. These principles and tactics are designed for the real world, where things inevitably do not always go right. The pillars are at once practical, sensible, and applicable in the hectic realities of the workplace because they focus on people, which you'll come to see as the most unstoppable force in a company's dynamic. The workforce doesn't have to settle for less any longer. Working together, we have the power to build a better tomorrow. Unite, and be invincible!s
Keywords: Computer science; Computer Science; Computer Science, general; Computing Milieux